Erradicar a pobreza extrema: Um objetivo ao alcance do Brasil - Rafael Guerreiro Osorio; Sergei Suarez Dillon Soares; Pedro Herculano Guimar\~aes Ferreira de Souza (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– In this text we address measurement, monitoring and cost issues relating to the eradication of extreme poverty in Brazil. We argue that, for the purpose of ending extreme poverty, income poverty is the relevant concept, and that an administrative extreme poverty line, decided upon politically, is the best criterion. For computational purposes, we use a R 67 extreme poverty line. The extreme poverty line should be updated using food inflation (INPC-alimentos) and progress should be assessed using the upcoming quarterly continuous household survey. We finally argue that families report incomes strategically, that even if correctly reported, all incomes are measured with error, and that those of poor people are also highly volatile. Given these limitations, the only way to ensure the end of extreme poverty is to give to extremely poor families a benefit close to the poverty line itself. We finally propose an incremental strategy that will cost less that 0,5% of GDP, using a R 67 line.
Keywords: I38; 330; Armutsbekämpfung; Brasilien